Multiple transportable carbohydrates during exercise: Current limitations and directions for future research - Wilson, P. B. (The Journal of Strength and Conditioning Research, 2015)
The concept of multiple transportable carbohydrates (MTC) refers to a combination of saccharides that rely on distinct transporters for intestinal absorption. Ingestion of MTC during prolonged exercise has been purported to increase carbohydrate absorption efficiency, increase exogenous carbohydrate oxidation, reduce gastrointestinal (GI) distress, and improve athletic performance when carbohydrate intake is high (>50-60 g/h). Although reviews of MTC research have been published previously, a comprehensive literature evaluation underscoring methodological limitations has not been conducted to guide future work. Accordingly, this review outlined the plausible mechanisms of MTC and subsequently evaluated MTC research based on several factors, including participant characteristics, exercise modality, exercise task, treatment formulation, treatment blinding, and pre-exercise nutrition status. A total of 27 articles examining MTC during exercise were identified and reviewed. Overall, ingestion of MTC led to increased exogenous carbohydrate oxidation, reduced GI distress, and improved performance during cycling lasting =2.5 hours, particularly when carbohydrate was ingested at =1.2 g/min. Despite the apparent benefits, several limitations in the literature were apparent, including that only 3 studies used running, only 2 studies were conducted in the field, most participants were fasted, and women and adolescents were underrepresented. In addition, the majority of the studies fed carbohydrate at =1.2 g/min, which may have inflated levels of GI distress and exaggerated performance decrements with single-saccharide feedings. Based on these limitations, future MTC investigations should consider focusing on running, examining team-based sports, including women and adolescents, conducting experiments under field conditions, examining the modifying effects of pre-exercise nutrition, and using modest feeding protocols (1.0-1.2 g/min).